Hadith #4266 - Sunan Abi Dawud - Abdullah bin 'Abdur Rahman b. Abi Sa'sa عبد الله بن عبد الرحمن بن أبي صعصعة; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abdur Rahman bin 'Abddllah bin 'AR عبد الرحمن بن عبد الله بن عبد الرحمن; Abu Sa'id al-Khudri; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
Ziyad, one who has white ears.
Grade: Sahih